Gender Gap in Agricultural Productivity: A Case Study of Smallholder Farmers in Busia County Kenya - Andele, Steve; Kiganda, Evans; Obange, Nelson (International Journal of Economics, 2024)
Purpose: The study aimed at determining the gender gap in agricultural productivity: A case of Smallholder Farmers in Busia Kenya. Methodology: The research employed a correlational research approach, utilizing multistage sampling to choose 384 participants from seven sub-counties within the study region. Data collection utilized structured questionnaires, and analysis was conducted on quantitative data using descriptive statistics and inferential methods with STATA version 17. The findings were presented using tables and figures. Findings: The study revealed a statistically significant gender gap in agricultural productivity in Busia-County at the expense of female farmers. Specifically in Teso North, gender gap was -0.43 with a p-value of 0.049, in Teso south, gender gap was -0.63 with a p-value of 0.040, in Bunyala, gender gap was -0.67 with a p-value of 0.035, in Butula, gender gap was -0.47 with a p-value of 0.002, in Matayos, gender gap was -0.72 with a p-value of 0.041, in Nambale, gender gap was -0.64 with a p-value of 0.041 and In Samia, gender gap was -0.67 with a p-value of 0.036. It was concluded that female farmers are less productive than male farmers in Busia County Kenya. Unique Contribution to Theory, Practice and Policy: Drawing from production theory, and social feminist theory, the study investigated the relationship between productivity and gender among smallholder farmers. To address the gender gap in agricultural productivity, it is recommended that policymakers, agricultural extension services, and other stakeholders advocate for gender-inclusive agricultural development initiatives in the area.